Anticancer therapeutic effect of ginsenosides through mediating reactive oxygen species - Li, Xiaonan; Cao, Donghui; Sun, Siming; Wang, Yuehui (Frontiers in Pharmacology, 2023)
Dysregulation of reactive oxygen species (ROS) production and ROS-regulated pathways in cancer cells leads to abnormal accumulation of ROS, displaying a double-edged role in cancer progression, either supporting transformation/proliferation and stimulating tumorigenesis or inducing cell death.Cancer cells can accommodate ROS by regulating them at levels that allow the activation of procancer signaling pathways without inducing cell death via modulation of the antioxidant defense system. Therefore, targeting ROS is a promising approach for cancer treatment. Ginsenosides, their derivatives, and related drug carriers are well-positioned to modulate multiple signaling pathways by regulating oxidative stress-mediated cellular and molecular targets to induce apoptosis; regulate cell cycle arrest and autophagy, invasion, and metastasis; and enhance the sensitivity of drug-resistant cells to chemotherapeutic agents of different cancers depending on the type, level, and source of ROS, and the type and stage of cancer. Our review focuses on the pro-and anti-cancer effects of ROS and summarizes the mechanisms and recent advances in different ginsenosides that bring about anticancer effects by targeting ROS, providing new ideas for designing further anti-cancer studies or conducting more preclinical and clinical studies. 1 reactions damage DNA, proteins, and lipids; thus, ROS are thought to be genomically damaging and cancer-promoting (Ismail et al., 2019). It has been well-established that almost all cancer cells exhibit variable types of oxidative stress and higher levels of ROS (Hayes et al., 2020). To adapt to high ROS levels and optimize their pro-cancer effects, carcinoma cells intelligently strengthen their antioxidant capacity to maximize their profitability during different stages (Reczek and Chandel, 2017b;Maslah et al., 2020;Attanasio et al., 2021). However, different opinions have been raised that ROS in cancers act as double-edged swords. ROS not only help cancer cell transformation/proliferation, but also exert cytotoxicity, activate anti-cancer signaling, and promote oxidative stress-induced cancer cell death (